Evaluating the Operational Efficiency of Jordan Islamic Bank and Housing Bank for Trade and Finance Using the ROE Model - Ezz Aldin Abu Daya (Journal of Islamic and Religious Studies, 2025)
This study critically assesses the operational efficiency of the Jordan Islamic Bank and the Housing Bank for Trade and Finance by applying the Return on Equity (ROE) framework over the period 2021–2023. A suite of financial performance indicators—including Return on Assets (ROA), Asset Utilization (AU), Equity Multiplier (EM), and Profit Margin (PM)—were employed to conduct a comparative analysis of both banks. The findings indicate that the Jordan Islamic Bank achieved notable growth in ROE during 2022, followed by a marginal decline in 2023, whereas the Housing Bank maintained consistent and stable ROE throughout the period. In terms of ROA, the Jordan Islamic Bank experienced a decline in 2023, signaling reduced efficiency in asset deployment, while the Housing Bank demonstrated continuous improvement. Asset Utilization for the Jordan Islamic Bank showed steady progress, contrasting with the fluctuating trend observed at the Housing Bank. The Equity Multiplier analysis revealed increasing financial leverage at the Jordan Islamic Bank, suggesting a heightened reliance on debt financing, while the Housing Bank displayed greater capital structure stability. Profit margin trends further reinforced these dynamics, with the Jordan Islamic Bank showing consistent improvement and the Housing Bank peaking in 2022 before a slight downturn in 2023. The integrated analysis offers valuable insights into each bank's strategic financial positioning and operational strengths. It is recommended that the Jordan Islamic Bank reevaluate its asset management practices, while the Housing Bank should focus on growth-oriented strategies to enhance long-term profitability.